Implementation of a Physical Activity Program Protocol in Schoolchildren: Effects on the Endocrine Adipose Tissue and Cognitive Functions - Diaz-Castro, Javier; Garcia-Vega, Jose Eulogio; Ochoa, Julio J.; Puche-Juarez, María; Toledano, Juan M.; Moreno-Fernandez, Jorge (Frontiers in Nutrition, 2021)
Practicing exercise is one of the best strategies to promote well-being and quality of life, however physical activity in schoolchildren and adolescents is developed in an unpredictable, intermittent way and in short periods. There are relatively few intervention studies investigating the role of physical activity in schoolchildren endocrine function of adipose tissue and cognitive function. 103 boys, divided into two groups: control, (n = 51, did not perform additional physical activity) and exercise (n = 52, performed vigorous physical activity after the regular school classes). The exercise group, developed a six months physical activity protocol delivered by the physical education teacher during the second term of the academic course. Body composition measurements, adherence to the Mediterranean diet, nutritional intake, hematological and biochemical parameters, endocrine function of the adipose tissue and biomarkers of brain molecular function were assessed at enrolment and after 6 months of intervention. No statistically significant differences between both groups were found for age, height and bone mass. Weight and BMI was lower in the exercise group compared to the control group, increasing lean mass and reducing fat mass. 58.68% of children in the exercise group showed high adherence to the Mediterranean Diet compared to 46.32% of the control group. The exercise group was more concerned about their diet consumed more fiber, vitamin B1, B2, B6, B12, D, Niacin, Folic acid, Fe, Zn, Se and Cu. Triglycerides levels and HDL-cholesterol were lower in the exercise group at the end of the study. Leptin, MCP-1, lipocalin-2, adipsin and PAI-1 levels were lower in the exercise group at the end of the exercise protocol. In contrast, adiponectin and osteocrin markedly increased in the exercise group. Moreover, marked increases were recorded in brain cognitive function biomarkers (NGF, BDNF and irisin) in the exercise group, which would have a positive impact on academic performance. Taken together, all the findings reported are consistent with many benefits of the exercise protocol on adipose tissue and brain molecular function, demonstrating the usefulness of early interventions based on physical activity in children to reduce risk factors related to sedentary lifestyle.